Development of a method of surface water content research using ultraviolet rays - Seidulla Abdullayev; Askar Abdykadyrov; Sunggat Marxuly; Gabit Bakyt; Aigul Baikenzheyeva; Kurmangazy Sarsanbekov (Journal of Environmental Engineering and Landscape Management)
It is known that the process of water treatment in surface water bodies requires the development of advanced and effective technologies for the destruction of harmful microorganisms and viruses. The aim of the present study is to develop a method for the investigation of surface water content. As a result of the study, the electronic circuit of the purification device using ultraviolet rays was developed. The energy and spectral characteristics were experimentally investigated and the economic efficiency of the ultraviolet ray device was determined, taking into account the basic sanitary and hygienic requirements for the organisation of ultraviolet water disinfection. It is substantiated, that the developed scheme provides safety of conditions of work of the personnel with the equipment.